An Analytical Study of Phrakrusangworasitthichote’s Educational Administration for Educational Equity among Highlander Youths - Saenmahayak, Phra Narongchai (The Journal of International Buddhist Studies College, 2023)
Educational Equity is one of the major global obstacles in delaying the achievement of UN’s Sustainable Development Goals (SDGs) by 2030. Like many other countries, Thailand has struggled to successfully bring all of its children into the educational system in an equitable way. While the government cannot render enough quality education services to underprivileged children, Phrapariyattidhamma School can help fill this gap. This study aimed: (1) to survey the status of educational administration at Wat Ban Khun Buddhist School, in Hod district, Chiang Mai Province and (2) to analyze the educational administration for educational equity of the school principal-Phrakrusangworasitthichote. The school is recognized as the leading Buddhist Scripture School in the Northern region rendering equitable basic education and Pāli study to underprivileged highland students since 2003. All students are treated fairly and inclusively. With competent teachers and conducive learning environment, the school has achieved the highest number of students who passed Pāli examination in Chiang Mai. The res applied a qualitative method and on-site investigation as research design. The research instrument was in-depth interview with 5 key informants utilizing the POSDCoRB theory as the analysis framework for 7 administration aspects, which included Planning, Organizing, Staffing, Directing, Coordination, Reporting and Budgeting. The results suggested that it is essential for school leaders to have a clear understanding and right approaches to cope with inequality in education and ability to orchestrate the staff, villagers, and local authorities to be voluntarily involved in the process of strengthening educational equity.